2020
DOI: 10.1177/0961203320935185
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and serum levels of adipokines in patients with systemic lupus erythematosus: a systematic review and meta-analysis

Abstract: Background We aimed to perform a systematic review and meta-analysis of studies assessing the homeostasis model assessment for insulin resistance (HOMA-IR) values, serum adiponectin, leptin and resistin levels in patients with systemic lupus erythematosus (SLE). Method Online databases were searched on 31 March 2019 in order to identify studies comparing HOMA-IR, serum adiponectin, leptin and resistin leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 37 publications
2
6
0
3
Order By: Relevance
“… 24 The causes of atherogenic dyslipidaemia in SLE are diverse, including insulin resistance and the inability of insulin to stimulate glucose metabolism. 25 Insulin resistance hinders the lipolysis and storage of fatty acids in adipocytes and alters the metabolic pathway dependent on PI 3 kinases which, among other functions, contribute to the degradation of apolipoprotein B. As a result of the massive supply of fatty acids and the defect in the degradation of apolipoprotein B, hypertriglyceridaemia and the atherogenic lipoprotein phenotype appear.…”
Section: Discussionmentioning
confidence: 99%
“… 24 The causes of atherogenic dyslipidaemia in SLE are diverse, including insulin resistance and the inability of insulin to stimulate glucose metabolism. 25 Insulin resistance hinders the lipolysis and storage of fatty acids in adipocytes and alters the metabolic pathway dependent on PI 3 kinases which, among other functions, contribute to the degradation of apolipoprotein B. As a result of the massive supply of fatty acids and the defect in the degradation of apolipoprotein B, hypertriglyceridaemia and the atherogenic lipoprotein phenotype appear.…”
Section: Discussionmentioning
confidence: 99%
“…This is attributed to the inflammatory nature of SLE and the use of corticosteroids as one of the important therapeutic modalities [ 57 - 58 ]. Kuo et al performed a systemic review and meta-analysis in 2020 with a total population of 4460 SLE patients who showed, when compared to controls, to have greater values of homeostasis model assessment for insulin resistance (HOMA-IR), standardized mean difference (SMD) of 0.425; 95% confidence interval (CI) 0.156-0.693; I2=93.8%, and higher levels of adiponectin (SMD=0.547; 95% CI 0.219-0.874; I2=90.1%), leptin (SMD=0.843; 95% CI 0.454-1.231; I2=94.4%), and resistin (SMD=0.856; 95% CI 0.199-1.513; I2=96.6%) with an association between serum resistin and SLE activity [ 59 ].…”
Section: Reviewmentioning
confidence: 99%
“…Recently, a possible association between systemic lupus erythematosus (SLE) and high rates of insulin resistance (IR) measured by the Homeostatic Model Assessment-Insulin Resistance (HOMA-IR) insulin resistance index 1,2 and metabolic syndrome (MetS) 3 has become a topic of interest. IR, defined as insulin-sensitive tissues decreased sensitivity or receptivity to insulin 4 , has been shown to be an independent risk factor for type 2 diabetes mellitus (T2DM) 5 , and can be present for years before the appearance of any changes in glycemic control.…”
Section: Introductionmentioning
confidence: 99%